2021
DOI: 10.3389/fonc.2020.600459
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Herceptin as a Potentially Valuable Adjuvant Therapy for a Patient With Human Epidermal Growth Factor Receptor 2-Positive Advanced Esophageal Squamous Cell Carcinoma

Abstract: Esophageal cancer is one of the most common cancers with a low overall 5-year relative survival rate of approximately 20%. Trastuzumab (Herceptin®) targets HER2 and is an effective therapeutic strategy in HER2-positive breast cancer. However, few reports have described targeted therapy for treating esophageal squamous cell carcinoma (ESCC). A patient with advanced ESCC who had received chemotherapy, radiotherapy, and had undergone a clinical study is described here. The tumor had not been controlled. Herceptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Trastuzumab, commercially known as Herceptin, is a Roche-developed HER2-targeted therapy that can directly treat HER2+ cancer cells, which are commonly overexpressed in breast and stomach cancer and have also been suggested to be present in esophageal cancer [ 74 ]. In EAC specifically, however, the literature has suggested that the presence of HER2+ in EAC ranges between 15% and 29% [ 75 ].…”
Section: Druggable Targetsmentioning
confidence: 99%
“…Trastuzumab, commercially known as Herceptin, is a Roche-developed HER2-targeted therapy that can directly treat HER2+ cancer cells, which are commonly overexpressed in breast and stomach cancer and have also been suggested to be present in esophageal cancer [ 74 ]. In EAC specifically, however, the literature has suggested that the presence of HER2+ in EAC ranges between 15% and 29% [ 75 ].…”
Section: Druggable Targetsmentioning
confidence: 99%
“…7,8 Traditional standard first-line therapy for advanced or metastatic esophageal cancer is doublet platinumbased chemotherapy with median overall survival (OS) about 1 year, [9][10][11][12][13][14][15] while combining human epidermal growth factor receptor 2 (HER2) antibody with the standard chemotherapy is recommended for HER2 positive GAC. 16 A case report demonstrated the promising treatment effect of adding anti-HER2 to chemotherapy in HER2-positive ESCC, 17 but relevant randomized trials are lacking largely due to the very low HER2positive rate in ESCC. 18,19 There is no evidence that targeted therapies are of clinical significance in phase III trials regarding advanced or metastatic ESCC.…”
mentioning
confidence: 99%